ANALISIS UNSUR INTRINSIK CERPEN â€œDILARANG MENYANYI DI KAMAR MANDIâ€ KARYA SENO GUMIRA AJIDARMA - Nurrachman, Ilham; Wikanengsih, Wikanengsih; Mahardika, Reka Yuda (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The purpose of this research is to analyze the intrinsic elements of a literary work. Literature is an essay from the results of human thoughts and feelings that arouses imagination. Literary work is a work that examines various problems of life. But in it has its own element of beauty. The type of literary work that is often read and describes a life is short stories. The short story length is very relative and in the short story it has elements that are different from other elements, the elements that are owned are the intrinsic elements. Intrinsic elements include themes, characters, plot, setting, point of view, and mandate. The method used by researchers is a qualitative descriptive method. This method aims to describe the facts in a short story. Researchers are interested in researching a short story entitled "Dilarang Menyanyi Di Kamar Mandi" by Seno Gumira Ajidarma, because this short story is a realist in telling social life that is easily carried away by other people's opinions and comments. This research produces intrinsic elements which include the themes contained in this short story including moral and social themes, the characters and their characterizations are divided into several with various kinds of characters available, the plot formed in this short story is a forward flow, the background used is in a the village alley and the mandate contained in this short story is the importance of maintaining good manners in terms of the new culture and culture so as not to cause misunderstandings so that far from social inequality, you must be able to understand the culture and culture of a place.